HBR'S 10 must reads: The definitive management ideas of the year from Harvard Business Review 2017. - Harvard Business School (Harvard Business Review Press, 2017)
HBR's 10 must be read series is the definitive sollection of ideas and best practices for aspiring and experienced leaders alike. These books offer essential reading selected from the pages of Harvard Business Review on topics critical to the success of every manager. The situation is over the past two decades, the amount of time managers and employees spend on collaborative work has ballooned. At many companoes people now spend about 80% of their time in meetings or aswering cilleagues' requests. The problem is although the benefits of colaboration are well documented, the costs often go unrecognized. When demands for collaboration run too high or aren't spread evenly through the organization, workflow bottlenecks and employee burnout result. The solution is leaders must learn to better manage collaboration in their companies by mapping supply and demand, eliminating or resistributing work, and incentivizing people to collaborate more efficiently.